Crop sensitivity to salinity - Katerji N.; van Hoorn J.W.; Mastrorilli M.; Hamdy A. (Non-conventional water use: WASAMED project, 2005)
In this paper, we shortly review the latest studies that, by combining agronomic and eco-physiological survey techniques into a multi-disciplinary approach, have allowed interpreting the relationships between salinity, plant growth and yield directly in the field. Among the different stress indicators, maximum leaf water potential of the day (measured ad pre-dawn) is the most reliable one. Clearer indications were provided by the Water Stress Day Index (the average of the differences of pre-dawn water potential measured during the growth cycle on two identical crops, but irrigated with water of different salinity). The relationship between WSDI and relative yield was proposed as criteria to classify the cultivated species. Using this method, only two groups of crops are classified: tolerant species (durum wheat, sugar beet, maize,...) and sensitive species (tomato, soy bean, broad bean,...). This classification of crop sensitivity to salinity is based on different observations independent of each other.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)